The chemistry and biology of guanidine secondary metabolites - Berlinck, Roberto G. S.; Bernardi, Darlon I.; Fill, Taicia; Fernandes, Alessandra A. G.; Jurberg, Igor D. (Natural product reports, 2021)
Covering: 2017–2019 Guanidine natural products isolated from microorganisms, marine invertebrates and terrestrial plants, amphibians and spiders, represented by non-ribosomal peptides, guanidine-bearing polyketides, alkaloids, terpenoids and shikimic acid derived, are the subject of this review. The topics include the discovery of new metabolites, total synthesis of natural guanidine compounds, biological activity and mechanism-of-action, biosynthesis and ecological functions.